Students’ perceptions of teachers’ translanguaging practices in Indonesian EFL classrooms - Fadila, Deandra Jeihan; Agustin, Dery Tria; Widagsa, Rudha; Yana, Pramugara Robby (Universitas Ahmad Dahlan, 2024)
In Indonesia, where more than 700 languages exist, EFL teachers make use of students’ linguistic repertoire (e.g., utilize the Indonesian language [hereafter ‘Indonesian’] which functions as the national and official language) during the English instruction. While previous studies have focused on various aspects of EFL teachers’ cognition, little has been known concerning students’ perceptions of teachers’ utilization of languages other than English during the EFL instruction. Therefore, the present study aims to further understand this issue by investigating students’ perceptions of translanguaging practices performed by their teachers during English lessons at a junior high school in Yogyakarta. A qualitative study with case study design was conducted to address the objectives. Three teachers’ classroom practices were observed and five students were purposively invited for interviews. Results showed that translanguaging practices performed by the teachers functioned as explanatory and rapport-building strategies. While students demonstrated positive attitudes towards such practices and stated that the teachers’ translanguaging practices supported their learning goals and helped to boost their motivation in language learning, they seemed to be concerned that uses of languages other than English during English lessons would not only reduce their exposure to the target language but also decrease their opportunities to improve their English-speaking skills.